Kidney thrombotic microangiopathy in lupus nephritis: Impact on treatment and prognosis. (September 2022) - Massicotte-Azarniouch, David; Kotzen, Elizabeth; Todd, Sarah; Hu, Yichun; Hogan, Susan L.; Jain, Koyal
Introduction: Lupus nephritis (LN) may present with thrombotic microangiopathy (TMA) on kidney biopsy, the impact of which on outcomes is unclear. This study examined the prognostic importance of LN with TMA on kidney biopsy, including response to therapy and long-term outcomes. Methods: We conducted a single-center, retrospective study of all cases of LN with concomitant TMA on kidney biopsy in the Glomerular Disease Collaborative Network database. Controls were individuals with LN without TMA matched to cases based on demographic and clinical variables. Outcomes were remission at 6- and 12-months, end-stage kidney disease (ESKD) and death. Logistic regression and Cox proportional hazards models were used to ascertain the risks for outcomes, with adjustment for serum creatinine and proteinuria. Results: There were 17 cases and 28 controls. Cases had higher creatinine, higher proteinuria and greater chronicity on biopsy at baseline compared to controls. The rates of remission at 6-months and 12-months were similar between cases and controls (6-months 53.9% vs 46.4%, adjusted OR 2.54, 95% CI 0.48, 13.37; 12-months 53.9% vs 50.0%, adjusted OR 2.95, 95% CI 0.44, 19.78). Cases were at greater risk for ESKD in univariate analysis (HR 3.77; 95% CI 1.24, 11.41) but not when adjusting for serum creatinine and proteinuria (HR 2.20; 95% CI 0.63, 7.71). There was no significant difference in the risk of death between cases and controls. Conclusion: Lupus nephritis with renal TMA likely responds to therapy similarly to those without TMA; risk for ESKD is not significantly increased, although the influence of renal function and proteinuria in larger samples is needed.